Water Level Monitoring System for Plain Area Affected by Topography - Halim, Muhammad Syakir; Saparudin, Faiz Asraf (Progress in Engineering Application and Technology, 2024)
The Muar River catchment faces recurrent, severe flood events exacerbated by rapid development. This research introduces Gezeiten Technology (GZ), a Water Level Monitoring system for the plain areas alongside the Muar River. GZ aims to provide a user-friendly flood management approach, helping communities anticipate and mitigate flood impacts. The system employs NodeMCU modules to send water level sensor data to the cloud, enabling real-time monitoring and early precautions in flood hotspots.